Pengaruh Keberadaan Outlet dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Kepercayaan Merek Pada Konsumen Jamu Nyonya Meneer di Kota Semarang - Septiyana, Dwi Agni; Hermani, Agus; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research aims to know the influence of the outlet and product quality toward purchase decisions through brand trust of herbal medicine consumers of Nyonya Meneer in Semarang. This type of research is explanatory, to explain the causal relationship between the outlet and product quality toward purchase decisions. Population ini this research is Nyonya Meneer consumers who was 16 until 35 years and live in Semarang. The number of samples in this study amounted to 100 people. The sampling on this study is used purposive sampling’method. Data collection methods used is literature studies and questionnaires. The data obtained were analyzed using a test of validity, reliability, simple linear regression and multiple linear regression. While hypothesis testing using t-test, F test and path analysis. The results showed that outlet and product quality affects purchase decisions. Based on the path analysis, its show that direct effect of outlet toward purchase decisions is 0,122. Meanwhile, the impact of outlet toward purchase decisions through brand trust is 0,027192. Its show that the impact of outlet toward purchase decisions is higher though not through the brand trust. In the other side, the direct effect of product quality toward purchase decisions is 0,126. Menawhile, the impact of product quality toward purchase decisions through brand trust is 0,032857. Its show that the impact of product qulity toward purchase decisions is higher though not through the brand trust. Based on this analysis, the advice that can be given to improve the brand trust or purchase decisions is that the PT Nyonya Meneer and the outlets owner should be able to improve the outlet with improving the desain and facilities outlet. And then to maintain product quality by improve quality packaging and the addition of variants taste. And to be able to invite young consumers, Nyonya Meneer can also add activities involving young consumers.But, based on the path analyse showed that coefficient has small number, so its better to the company also give the attention to other factors that impact the purchase decisions.